A Splicing Technique for Image Tampering using Morphological Operations - Gaffar, Achmad Fanany Onnilita; Supriadi, Supriadi; Saputra, Arief Bramanto Wicaksono; Malani, Rheo; Wajiansyah, Agusma (Signal and Image Processing Letters, 2019)
Image tampering is one part of the field of image editing or manipulation that changes certain parts of the graphic content of a given image. There are several techniques commonly used for image tampering, such as splicing, copy-move, retouching, etc. Splicing is a type of image tampering technique that combines two different images, replacing particular objects, skewing, rotation, etc. This study applies the splicing technique to image tampering using morphological operations.Â  Morphology is a collection of image processing operations that process images based on their shape. The aim of this study is to replace particular objects in an original image with other objects that are similar to another selected image.Â  In this study, we try to replace the ball object in the original image with another ball object from another image